Tourism and Travel during the Cold War Negotiating Tourist Experiences across the Iron Curtain (Taylor & Francis, 2019)
The Iron Curtain was not an impenetrable divide, and contacts between East and West took place regularly and on various levels throughout the Cold War. This book explores how the European tourist industry transcended the ideological fault lines and the communist states attracted an ever-increasing number of Western tourists. Based on extensive original research, it examines the ramifications of tourism, from sun-and-sea package tours to human rights travels, in key Eastern European locations including East Berlin, the Soviet Union, Yugoslavia, and Albania. The book's analysis of the politics, culture, and history of tourism to the East offers important new perspectives on European tourism in the twentieth century.
English
Keywords: cold war; experiences; iron curtain; thema EDItEUR::J Society and Social Sciences; thema EDItEUR::N History and Archaeology::NH History; tourism; tourists; travel